Psychological and stigma profiles of HIV patients in a North-Central city of Nigeria - Abdullahi Ahmed; Medinat O Osinubi; Mojirola M Fasiku; Muhammed M B. Uthman; Tolulope Soyannwo; Saheed O Jimoh; Tope Olubodun (Journal of Family Medicine and Primary Care, 2022)
Background: The World Health Organization defines health as a state of complete physical, mental, and social well-being and not merely the absence of infirmity and disease. Researchers and clinicians have mainly focused on health outcomes that are physically or laboratory measured. These, however, do not reflect how the affected individual feels and functions in daily life. This study assessed the psychological and stigma profiles of patients attending HIV clinics in a North-central State of Nigeria. Methods: The study design was descriptive cross-sectional. A total of 384 HIV-positive patients who were systematically recruited at 5 public service delivery sites in Ilorin, Kwara State, North-central Nigeria participated in the study. Data was analyzed using SPSS software version 20.0. Level of significance was pre-determined at P value < 0.05 at a confidence level of 95%. Results: Fifty-nine percent of respondents reported being anxious about their condition and 25.5% felt depressed. Eighty-six percent received adherence counselling and 82.3% received psychological care from support groups. In the psychological domain, majority (74.5%) of the respondents had high health-related quality of life (HRQoL). There was a statistically significant association between employment status and psychological domain of HRQoL. As regards stigma, majority experienced high stereotype stigma (73.7%) and 67.2% experienced high stigma as pertains disclosure. Conclusion: Health workers should promote psychological support of HIV patients, for example, in form of support groups and adherence counseling. Efforts by government and corporate bodies should be geared towards employment empowerment of PLWHA which may help improve quality of life.